Chitinase and indoleamine 2, 3-dioxygenase are prognostic biomarkers for unfavorable treatment outcomes in pulmonary tuberculosis - Kumar, Nathella Pavan; Nancy, Arul; Viswanathan, Vijay; Sivakumar, Shanmugam; Thiruvengadam, Kannan; Ahamed, Shaik Fayaz; Hissar, Syed; Kornfeld, Hardy; Babu, Subash (Frontiers in Immunology, 2023)
Chitinase, Indoleamine 2,3-dioxygenesae-1 (IDO-1) and heme oxygenase-1 (HO-1) are candidate diagnostic biomarkers for tuberculosis (TB). Whether these immune markers could also serve as predictive biomarkers of unfavorable treatment outcomes in pulmonary TB (PTB) is not known. A cohort of newly diagnosed, sputum culture-positive adults with drug-sensitive PTB were recruited. Plasma chitinase protein, IDO protein and HO-1 levels measured before treatment initiation were compared between 68 cases with unfavorable outcomes (treatment failure, death, or recurrence) and 108 control individuals who had recurrence-free cure. Plasma chitinase and IDO protein levels but not HO-1 levels were lower in cases compared to controls. The low chitinase and IDO protein levels were associated with increased risk of unfavourable outcomes in unadjusted and adjusted analyses. Receiver operating characteristic analysis revealed that chitinase and IDO proteins exhibited high sensitivity and specificity in differentiating cases vs controls as well as in differentiating treatment failure vs controls and recurrence vs controls, respectively. Classification and regression trees (CART) were used to determine threshold values for these two immune markers. Our study revealed a plasma chitinase and IDO protein signature that may be used as a tool for predicting adverse treatment outcomes in PTB.